Trajetórias e memórias em Raul Seixas: matrizes e formação da construção poético-musical da Metamorfose Ambulante (1957 a 1972) - Santos, Paulo dos (2021)
This thesis investigates the trajectory of Raul Seixas between the years of 1957 and 1972, considered the moment of his poetic-musical training. The research covers a wide variety of documents, for instance, his discography, presentations, interviews and artist’s testimonials on the radio, the television and the print media; as well as testimonials from people related to Raul, that is, both his family and friends. This doctorate was developed under the perspective of Cultural History and History and Music. It retrieves questions from the musical movements involving young people, such as Rock’n’Roll, including the Beatles and Bob Dylan, with their protest songs. Furthermore, particularly in the Brazilian context, it observes cultural movements, namely Bossa Nova, Tropicalismo and Jovem Guarda. Likewise, it highlights the process of cultural circularity through the disc, Cinema, Radio and TV, expanding the dynamics of a Young Culture. In the same way, it also contextualizes the tensions of the Cold War, the struggle for black civil rights, the feminist movement, the hippies and the counterculture. In Brazil, the changes in the political scenario of the Dutra and JK governments, the 1964 coup and the military governments; moreover, the implementation of the AI-5, in 1968. The analysis is organized into four chapters. The first emphasizes Raul Seixas’ education, his childhood, school education, daily life in Salvador and the philosophical and musical matrices. The second chapter still aims to find the formation elements, which are identified by many specialists and critics as a hybridism between Rock’n’Roll and Baião. Therefore, discussions about generation and youth are incorporated, the artist's choice for a musical career, the constitution of musical groups, their performances in the bahian capital and involvement with the Jovem Guarda movement (Jerry Adriani, Wanderley Cardoso, Roberto Carlos, among others). In addition, this thesis includes his first career attempt in Rio de Janeiro, the recording of the LP Raulzito e os Panteras, the failure of the undertaking and his return to Salvador. Thereafter, Raul's trajectory stands out as he became a successful producer and composer in the pop fragment, the beginning of his solo career as a composer and singer, the release of the LP Sociedade da Grã-Ordem Kavernista Apresenta Sessão das Dez, his participation in the VII Festival Internacional da Canção (1972) and his meeting with Paulo Coelho, his future partner and interlocutor in the proposal of the Sociedade Alternativa